The influence of body position on Bielschowsky's test - Souza-Dias,Carlos R. (2014)
Purpose: To investigate the veracity of Jampolsky's statement that Bielschowsky's head tilt test is inverted if performed with the patient in the upside-down position and to interpret its neuromuscular mechanism. Methods: We present a series of 10 patients selected from a referred sample who were diagnosed with superior oblique paresis. Hypertropia was measured in the primary position, with the head erect and tilted toward both shoulders with the patient in the erect, supine, and upside-down positions. The last position was achieved by hanging the patient upside-down. Results: As expected, our results showed the veracity of Jampolsky's statement. The forced head tilt difference was inverted or significantly decreased when the test was performed in the upside-down position. Moreover, in all patients, Bielschowsky's phenomenon was neutralized in the supine body position, in which hypertropia with the head erect tended to vanish. In 3 patients, it disappeared completely. Conclusions: This study showed that, in patients with superior oblique paresis, differences in the extent of hypertropia in Bielschowsky's test tended to vanish when the test was performed with the patient in the supine position and invert when it was performed with the patient in the upside-down position.